Battery durability and reliability under electric utility grid operations: 20-year forecast under different grid applications. (June 2020) - Baure, George; Dubarry, Matthieu
Highlights: Different grid applications showed different impact on battery degradation mechanisms. 20-year forecast was possible from consideration of the silent degradation mechanisms. LTO based cells are well suited for grid storage applications. Abstract: As the number of battery energy storage systems increase, along with their grid applications, it has become imperative to better understand and predict battery cell degradation. Accurately forecasting their durability under different usage regimes has become a priority in determining the operational and commercial risks associated with BESS deployments. In this work, electrochemical data from a laboratory experiment mimicking different grid applications for two BESS deployed on the island of O'ahu and Moloka'i was analyzed. The results were extremely small capacity losses (<1%) after more than a year of testing but significant amounts of underlying "silent" degradations with incubation periods. The impact of these silent degradations was quantified and used to forecast 20-year usage. They were shown to induce, in some cases, an acceleration of the capacity loss after as low as 6 years of deployment.